49.9k views
5 votes
The difference between the roots of the equation 3x2+bx+10=0 is equal to 4 1 3 . find
b.

User Nathan Lee
by
5.9k points

2 Answers

4 votes

Answer:

The answer is 17 and -17

Explanation:

User Kevin Hernandez
by
5.9k points
5 votes
Given that the difference between the roots of the equation
3x^2+bx+10=0 is
4 (1)/(3) = (13)/(3).

Recall that the sum of roots of a quadratic equation is given by
- (b)/(a).

Let the two roots of the equation be
\alpha and
\alpha + (13)/(3), then


\alpha + \alpha + (13)/(3) =2 \alpha + (13)/(3) =- (b)/(a) =- (b)/(3) \\ \\ i.e.\ \ 2 \alpha + (13)/(3)=- (b)/(3) . . . (1)

Also recall that the product of the two roots of a quadratic equation is given by
(c)/(a), thus:


\alpha \left( \alpha + (13)/(3) \right)= \alpha ^2+ (13)/(3) \alpha = (c)/(a) = (10)/(3) \\ \\ i.e.\ \ \alpha ^2+ (13)/(3) \alpha=(10)/(3) . . . (2)

From (1), we have:


2 \alpha =- (b)/(3) - (13)/(3) \\ \\ \Rightarrow \alpha =- (b)/(6) - (13)/(6)

Substituting for alpha into (2), gives:


\left(- (b)/(6) - (13)/(6)\right)^2+ (13)/(3) \left(- (b)/(6) - (13)/(6)\right)= (10)/(3) \\ \\ \Rightarrow (b^2)/(36) + (13b)/(18) + (169)/(36) - (13b)/(18) - (169)/(18) = (10)/(3) \\ \\ \Rightarrow (b^2)/(36) - (289)/(36) =0 \\ \\ \Rightarrow (b^2)/(36) = (289)/(36) \\ \\ \Rightarrow b^2=289 \\ \\ \Rightarrow b=\pm√(289)=\pm17
User Roman Kazmin
by
6.7k points